2023
DOI: 10.3390/ijms24032617
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia in a Hungarian Female Patient with a Novel Variant of Unknown Significance in the CCDC88C Gene

Abstract: Spinocerebellar ataxia (SCA) 40 is an extremely rare subtype of the phenotypically and genetically diverse autosomal dominant ataxias caused by mutations of the CCDC88C gene. Most reported cases of SCA40 are characterized by late-onset cerebellar ataxia and variable extrapyramidal features; however, there is a report of a patient with early-onset spastic paraparesis as well. Here, we describe a novel missense CCDC88C mutation (p.R203W) in the hook domain of the DAPLE protein encoded by the CCDC88C gene that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…CCDC88C variations were also found in seven cases (15 individuals) with autosomal dominant spinocerebellar ataxia. These were all monoallelic and missense variants 13–19 …”
Section: Resultsmentioning
confidence: 99%
“…CCDC88C variations were also found in seven cases (15 individuals) with autosomal dominant spinocerebellar ataxia. These were all monoallelic and missense variants 13–19 …”
Section: Resultsmentioning
confidence: 99%
“…Yahia et al [22] reported a case on a Sudanese patient with childhood-onset spastic paraparesis without cerebellar signs caused by a missense mutation (c.1993G > A) in the CCDC88C gene. Boros, F. et al [23] reported a female patient carried a missense mutation (p.R203W) in CCDC88C who developed late-onset ataxia, dysmetria, and intention tremor. Taken together, these findings suggest that the clinical manifestations of SCA40 may be related to race, gene mutation sites, and other factors [24].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this gene mutation causes JNK hyperphosphorylation, upregulates caspase-3 activity, and induces apoptosis [9, 22]. However, studies have also shown that A mutations do not affect c-Jun N-terminal kinase 1 (JNK1) phosphorylation, nor do they trigger apoptosis signals, only a small-scale activation of the JNK pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…5 The p.Arg464Cys identified in our patient is also present in his unaffected mother who, however, has not yet reached the onset age of the majority of patients described with monoallelic CCDC88C variants. 6,7 It is possible that this variant alone is not sufficient to determine an early-onset phenotype and the presence of the second variant may have a role in the early manifestations that we observed in our patient. Had genetic information been available for Yahia et al's 3 case parents, this would help support the CCDC88C variant pathogenetic hypothesis.…”
mentioning
confidence: 86%